Autologous bone marrow transplantation in a dog with lymphoma: a clinical study - Cápua,Maria Luísa Buffo de (2009)
The objective of this study is to provide the first report of bone marrow transplantation (BMT) in dogs in Brazil. A Rottweiler with cutaneous lymphoma was submitted to a twelve-week Madison-Wisconsin chemotherapy protocol followed by autologous bone marrow transplantation. For this, 10mL kg-1 of bone marrow was collected simultaneously from both iliac crests and cryopreserved in a freezer at -80°C. The conditioning step was performed by administering cyclophosphamide by intravenous route at 400mg m-2. Bone marrow was reinfused after defrosting in a water bath at 37°C. Bone marrow nucleated cell counts before and after freezing, showed a small relative loss of nucleated cells (35.10 and 31.80x10³µL-1 , respectively). Cyclophosphamide induced neutropenia which was reverted by a granulocyte colony-stimulating factor (G-CSF) capable of stimulating hematopoetic reconstitution. On the day 360 after transplant the patient was found to be in complete remission. This study indicates that autologous BMT in a dog with lymphoma submitted to myelosuppressive chemotherapy was potentially safe and effective.